TEMA DAN FUNGSI BOTO-BOTOANG DALAM BAHASA MAKASSAR - Salmah Djirong (tuahtalino, 2021)
Boto-botoang is one of the literary works transmitted orally, from one generation to the next generation. This oral literature is still found nowadays; however, its study is still necessary for preserving it regarding the Makassar language usage is decreased caused by many factors. Thus, the problem of the writing is what function of boto-botoang is? What themes implied in boto-botoang are? The method conducted in writing is descriptive, using noting-listening techniques, interviews, and the library. Having been discussed, boto-botoang has several functions (1) as humor, (2) as entertaining, (3) as the game, (4) as sarcasm, while the themes are animal, human being, things around, and human being and their activity.